(untitled) (Semiárida, 2020)
The rain erosivity index (R factor) is an important element to estimate soil losses applying the universal soil loss equation (USLE). This factor was evaluated through Fournier’s index modified by FAO (1984) using the rainfall information from 51 localities of La Pampa province. The risks of rain erosivity (280 a 530 Tn ha-1 año-1) increase towards the North-East of this region and is greatest between February and March.